PENGARUH E-BILLING DAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK GAGAP TEKNOLOGI DI KABUPATEN TANA TORAJA - Dhea Giska (Jurnal Ilmiah Mahasiswa FEB, 2019)
E-billing and e-filing can pose a crucial challenge for technology illiterate taxpayers to comply with the taxation regulation. This study aims to reveal the effect of e-billing and e-filing on technology illiterate taxpayers’ compliance. The primary data are sourced from structured interviews conducted in Tana Toraja regency. The results of the analysis indicate that technology illiterate taxpayers are compliant with the taxation regulation despite their struggle to use the ebilling and e-filing system thanks to the device (i.e: smartphone and computer) and network service scarcity.Keywords: Taxpayers’ compliance, E-filing, E-billing